Linear ubiquitination of cytosolic Salmonella Typhimurium activates NF-[kappa]B and restricts bacterial proliferation - Wijk, Sjoerd van; Heilemann, Mike (Nature microbiology, 2017)
Ubiquitination of invading Salmonella Typhimurium triggers autophagy of cytosolic bacteria and restricts their spread in epithelial cells. Ubiquitin (Ub) chains recruit autophagy receptors such as p62/SQSTM1, NDP52/CALCOCO and optineurin (OPTN), which initiate the formation of double-membrane autophagosomal structures and lysosomal destruction in a process known as xenophagy. Besides this, the functional consequences and mechanistic regulation of differentially linked Ub chains at the host-Salmonella interface have remained unexplored. Here, we show, for the first time, that distinct Ub chains on cytosolic S. Typhimurium serve as a platform triggering further signalling cascades. By using single-molecule localization microscopy, we visualized the balance and nanoscale distribution pattern of linear (M1-linked) Ub chain formation at the surface of cytosolic S. Typhimurium. In addition, we identified the deubiquitinase OTULIN as central regulator of these M1-linked Ub chains on the bacterial coat. OTULIN depletion leads to enhanced formation of linear Ub chains, resulting in local recruitment of NEMO, activation of IKKα/IKKβ and ultimately NF-κB, which in turn promotes secretion of pro-inflammatory cytokines and restricts bacterial proliferation. Our results establish a role for the linear Ub coat around cytosolic S. Typhimurium as the local NF-κB signalling platform and provide insights into the function of OTULIN in NF-κB activation during bacterial pathogenesis.